PERAN KADER KAMPUNG KB PADA MASA PANDEMI COVID 19 - Aditya Farit Subekti (Jurnal Delima Harapan, 2022)
Kampung KB is an integrated development program population, family planning, as well as related sector development in an effort to improve quality of life for families and communities. Kampung KB’s cadres, are volunteers who are chosen to help organize population and family planning programs. This study knowing aims to role of kb village cadres in socializing preganancy distance arrangements during Pandemic. type of this research is descriptive This research is classified as using a qualitative research design. informants in this research amounted to 4 representative cadres of each RW chosen by Key Person. data collection in this research used a source triangulation technique with in-depth interviews and activity documentation. Results research are characteristics Kampung KB’s cadres in Tegaren Village are quite good, supported by self-motivation, as well support from local community and religious leaders, although in this case there are no binding rules to help performance of cadres. In addition, it is known that even during pandemic, cadres still continue to socialize and education community by door to door to help regulate distance between pregnancies in community. conclusion in this research is cadres continue to carry out their duties to socialize pregnancy distance and use of contraceptives as well as health monitoring community by door to door. In research, it is recommended for cadres to further increase their resource potential.